Conceptualización de un corredor ecológico vial en Bogotá (2007)
Ecological corridor implementation is one the most popular conservation strategies to facilitate movement of ecological processes in fragmented landscapes. The reliability of corridorplanning depends on economic, social and biophysical variables that change from one place to another. The objective of this paper is to present a methodological approach to implement an ecological corridor along Bogotá – Villavicencio Highway, taking into consideration the participation of community near the project, the biophysical conditions ofthe area and the technical limitations to plant vegetation close to the engineering structures.